A new human 3D-liver model unravels the role of galectins in liver infection by the parasite Entamoeba histolytica. - Debora B Petropolis (Public Library of Science (PLoS), 2014)
Investigations of human parasitic diseases depend on the availability of appropriate in vivo animal models and ex vivo experimental systems, and are particularly difficult for pathogens whose exclusive natural hosts are humans, such as Entamoeba histolytica, the protozoan parasite responsible for amoebiasis. This common infectious human disease affects the intestine and liver. In the liver sinusoids E. histolytica crosses the endothelium and penetrates into the parenchyma, with the concomitant initiation of inflammatory foci and subsequent abscess formation. Studying factors responsible for human liver infection is hampered by the complexity of the hepatic environment and by the restrictions inherent to the use of human samples. Therefore, we built a human 3D-liver in vitro model composed of cultured liver sinusoidal endothelial cells and hepatocytes in a 3D collagen-I matrix sandwich. We determined the presence of important hepatic markers and demonstrated that the cell layers function as a biological barrier. E. histolytica invasion was assessed using wild-type strains and amoebae with altered virulence or different adhesive properties. We showed for the first time the dependence of endothelium crossing upon amoebic Gal/GalNAc lectin. The 3D-liver model enabled the molecular analysis of human cell responses, suggesting for the first time a crucial role of human galectins in parasite adhesion to the endothelial cells, which was confirmed by siRNA knockdown of galectin-1. Levels of several pro-inflammatory cytokines, including galectin-1 and -3, were highly increased upon contact of E. histolytica with the 3D-liver model. The presence of galectin-1 and -3 in the extracellular medium stimulated pro-inflammatory cytokine release, suggesting a further role for human galectins in the onset of the hepatic inflammatory response. These new findings are relevant for a better understanding of human liver infection by E. histolytica.